What do patients want from high-quality general practice and how do we involve them in improvement? - Coulter, A; Elwyn, G (2002)
Patient involvement is being encouraged by the government and by others as a way of improving the quality of the service provided in general practice. Patients can be involved in their own individual care; for example, in treatment decision making and in disease management; or collectively, by providing feedback on aspects of practice organisation and quality. Active participation in treatment decisions and in self management of chronic conditions can benefit patients in the short-term and may lead to better health outcomes in the longer term, although the evidence for this is currently equivocal. However, the ethical and societal arguments in its favour seem overwhelming. Helping patients to help themselves makes sense for general practitioners as well. Strengthening patients' coping skills could help to reduce inappropriate demands on their time. Involving the public in quality improvement activities has become a key policy direction, and trusts will be required to survey their patients on an annual basis. The proposed new general practitioner contract has recognised the importance of the patient's perspective in its quality framwork. Practices that want to anticipate these trends should look for patient survey instruments to obtain feedback on their organisation and the interpersonal skills of the clinicians.